Women in seafood processing. - Gopal, Nikita (Yemaya : ICSF'S Newsletter on Gender and Fisheries)
A study carried out in Gujarat, India finds that changes in the infrastructure of seafood processing plants post globalization has not really changed the status of the women workers in the industry.